“Fuck yeah!” : Studying Functions and Translation Strategies of Swearing in English and Finnish Fansubtitles - Tolppanen, Jonna (fi=Turun yliopisto|en=University of Turku|, 2018)
This Master’s Thesis studies the functions of swearing and the translation strategies which can be employed when translating swearing. The aim is to examine the possible translation strategies, and how the functions and translation strategies are realized in the English and Finnish fansubtitles of The United States of Tara. Some studies on fansubtitles exist, but the topic still calls for more research, which is one motivation for focusing on them, alongside with the fact that fansubtitles sometimes include creative translation solutions. The study is two-fold in nature: the functions of swearing were examined from the English subtitles, and the translation strategies from the Finnish subtitles. This was due to the different nature of the subtitles, which made fair comparisons impossible. The two-fold nature of the study demonstrates the complex nature of swearing, and provides a more comprehensive account on what swearing is, since even defining swearing comprehensively is extremely difficult, as discussed in the thesis. The categorizations of functions and the translation strategies are based on previous research by Andersson and Trudgill, Mohr, Dynel, Sobón, and Leppihalme. The study requires assessment of the force of swearwords, in which two monolingual dictionaries, The Merriam-Webster dictionary and Kielitoimiston sanakirja, are employed. All data were gathered manually by viewing the episodes multiple times without and with each set of subtitles. The instances of swearing were listed in a table in full sentences to preserve the immediate textual context. Moreover, the original spoken sentence was transcribed into the same table for easy comparison. The study found that expressing feelings is closely connected to swearing. Furthermore, swearing can be important even when it does not express feelings, for example for characterization. Some of the examined functions were very rare or non-existent in the data. All the examined translation strategies occurred in the data at least two times, but the two most common ones were omission and retention. A lot of swearing was lost in the Finnish subtitles, often due to condensing and idiomaticity. The data mostly employed only a few swearwords, for example fuck, shit, hitto and helvetti, although some creativity was observed in the abusive swearing category. The study demonstrated how context affects the interpretation of the function and force of swearing; for example, if said in a different tone of voice, the same swearword can express different feelings. In fact, context is a crucial factor in the study, and its involvement is discussed continuously throughout the thesis.